2006
DOI: 10.1002/pmic.200600282
|View full text |Cite
|
Sign up to set email alerts
|

Membrane microdomains and proteomics: Lessons from tetraspanin microdomains and comparison with lipid rafts

Abstract: Biological membranes are compartmentalized into microdomains that exhibit particular lipid and protein compositions. Membrane microdomains, such as tetraspanin-enriched microdomains and lipid rafts, have been suggested to play a role in a variety of physiological and pathological processes. Therefore, the characterization of the protein compositions of these microdomains, which is the focus of this review, appears to be a crucial step to better understanding their function. Proteomics has recently allowed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 77 publications
0
100
0
Order By: Relevance
“…The recovery of membrane microdomains in exosomes is of particular interest with respect to tetraspanins, which organize clusters of tetraspanins, additional transmembrane proteins, and membrane-proximal signaling proteins, such as integrins, G protein-coupled receptors, proteases, and protein kinase C (10,(18)(19)(20). Prominent Tspan8 partners are CD13, EWI-F, intersectin-2, EpCAM, CD49c, and CD104 (21).…”
Section: Introductionmentioning
confidence: 99%
“…The recovery of membrane microdomains in exosomes is of particular interest with respect to tetraspanins, which organize clusters of tetraspanins, additional transmembrane proteins, and membrane-proximal signaling proteins, such as integrins, G protein-coupled receptors, proteases, and protein kinase C (10,(18)(19)(20). Prominent Tspan8 partners are CD13, EWI-F, intersectin-2, EpCAM, CD49c, and CD104 (21).…”
Section: Introductionmentioning
confidence: 99%
“…Integrins are known to interact strongly with other adhesion molecules on the cell's surface, especially via lipid rafts. 7 Although CD49d is the specific target of natalizumab, and therefore is logically modulated on the cells, our results suggest that this disruption of one integrin may also alter the expression of other adhesion molecules. The net result could therefore be, as expected, a defective stimulation potential of B and T cells, along with decreased migration capacities across the blood-brain barrier.…”
mentioning
confidence: 84%
“…They are considered as physically Journal of Cell Science 123 (5) and functionally distinct from lipid rafts (Boucheix et al, 2004;Hemler, 2003) but they depend at least in part on lipids, including gangliosides (GM) and cholesterol (Charrin et al, 2003b). It has been shown that CD82 increases surface expression of several gangliosides and associates with and regulates cholesterol-rich microdomains (Charrin et al, 2003b;Delaguillaumie et al, 2004;Hemler, 2003;Le Naour et al, 2006). Moreover, cholesterol has a role in the diffusion of EGFR since its depletion led to almost complete confinement of the receptors (Orr et al, 2005).…”
Section: Role Of Cd82 In Egf/egfr Dynamics and Endocytosismentioning
confidence: 99%